2004
DOI: 10.1038/sj.onc.1207444
|View full text |Cite
|
Sign up to set email alerts
|

Androgens target prohibitin to regulate proliferation of prostate cancer cells

Abstract: Proteins involved in the growth response of prostate cancer cells to androgen were investigated by comparing the proteomes of LNCaP cells treated with vehicle or androgen. Whole-cell lysates were separated by twodimensional PAGE, and HPLC-MS/MS was used to identify androgen-regulated proteins. Prohibitin, a protein with cell-cycle regulatory activity, was shown to be downregulated by 50% following androgen stimulation. Western blot and reverse transcription-PCR experiments confirmed the result and showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
77
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 42 publications
14
77
1
Order By: Relevance
“…14). In support of this, we have previously demonstrated that the AR in these cells is capable of downregulating endogenous prohibitin protein in response to androgen stimulation, to a similar extent as seen in the LNCaP cell line (18).…”
Section: Resultssupporting
confidence: 60%
“…14). In support of this, we have previously demonstrated that the AR in these cells is capable of downregulating endogenous prohibitin protein in response to androgen stimulation, to a similar extent as seen in the LNCaP cell line (18).…”
Section: Resultssupporting
confidence: 60%
“…Cell Proliferation Assays-Sulforhodamine B was used to assess proliferation of cells as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…5,6 PHB can also inhibit steroidactivated nuclear receptors, such as the androgen receptor (AR) and estrogen receptor (ER). 7,8 PHB was reported to act as a potent transcriptional co-repressor of ERa and associate with estrogen-regulated promoters in the absence of hormone, dissociating after hormone treatment in the breast cancer cells. 8 PHB was reported to induce the anti-proliferative actions of estrogen antagonists in breast cancer cells and recruit BRG1-containing chromatin-remodeling complex to antagonist-bound AR in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%